THE HANDLING OF BAD CREDIT AT KOPERINDO EAST JAVA, KANDAT DISTRICT, KEDIRI REGENCY - Yusuf, Saifudin; Murdinar, Hardining Estu; Suprajang, Sandi Eka (DIVERSITY Logic Journal Multidisciplinary, 2023)
Background. Koperindo East Java activities collect funds from the public in the form of savings and channel these funds back to the community in the form of credit and provide other bank services. Research Purpose. This study aims to analyze the percentage level of bad credit at Koperindo and describe Non-Performing Loans (NPL) for the last 3 years. Research Methods. This descriptive research at Koperindo East Java, Kandat District, Kediri Regency. This study used primary data sources by interviews and field observations. Researchers also used secondary data obtained through Koperindo banking documents and analyzed them using descriptive analytic methods. Findings. Bad credit is caused by internal factors and external factors in Koperindo. For 2020 it has an NPL of 7.42%, for 2021 it has an NPL of 9.97%, this shows that in 2022 NPL credit will increase by 2.25%. Because the NPL level at Koperindo East Java exceeds the policy standard, which is 5%, Koperindo emphasizes that in 2021 it will focus more on NPL so that cooperatives experience a decrease in the NPL level. So that in 2022 the NPL is 3.75% and has decreased by 6.22%. The NPL principle is “The Lower Is Better”, meaning that the smaller the NPL value, the better the soundness level of a cooperative. Conclusion. Handling bad credit problems through optimal and effective billing by the credit supervisory team and restructuring in 3 ways: extending the credit period, changing the loan system from the installment system to maturity, and confiscating collateral.